Why Risk Perception Matters: Exploring Internet Altruistic Behavior: Mengapa Persepsi Risiko Penting: Menjelajahi Perilaku Altruistik di Internet - Hafizah, Nasywa; Syahrina, Kartika; Aiyuda, Nurul; Zikrinawati, Khairani (Psikologia : Jurnal Psikologi, 2025)
The times have changed the pattern of human behavior, including in the scope of the internet. Along with the development of digital technology, a new phenomenon has emerged that has attracted the attention of researchers, namely Internet Altruistic Behavior (IAB). Internet Altruistic Behavior (IAB) is a form of altruistic behavior that occurs online, where individuals provide assistance to others without expecting direct rewards. Unlimited internet access in digging up information causes risk perception to be very important. Risk perception is an individual's perspective in assessing and understanding the potential losses that may occur in a particular situation. It involves a subjective assessment of the level of that risk to them. Errors in risk perception can make individuals misjudge the level of safety that can affect their decision to participate in altruistic behavior. The research method used in this study is quantitative. The subjects in this study were individuals who actively use the internet with an age range of 17 years - 29 years with a total of 142 subjects. Data were collected using quota sampling technique. The results in this study indicate a significant negative relationship between risk perception and internet altruistic behavior. The results of hypothesis testing obtained a correlation coefficient of r = -0.542 with a significant p = 0.000 (p < 0.05). These results indicate that the higher the risk perception, the lower the Internet altruistic behavior in individuals. Highlights: Negative Correlation – Higher risk perception is linked to lower Internet Altruistic Behavior (IAB), as individuals hesitate to help due to perceived risks. Role of Risk Perception – Misjudging online risks can impact decisions, leading to reduced participation in altruistic acts. Study Findings – Research on 142 internet users (ages 17-29) using quantitative methods confirms a significant negative relationship (r = -0.542, p = 0.000) between risk perception and IAB. Keywords: Risk Perception, Altruistic Behavior, Internet